A quality improvement project reduces time spent at an inflammatory bowel disease infusion center with accelerated infliximab infusion protocol. Issue 7 (1st June 2022) - Ong, Wan Chee; Lim, Miao Shan; Chan, Elaine; Lim, Thomson Chong Teik; Lim, Teong Guan; Chan, Webber
Abstract: Background and Aim: Patients with inflammatory bowel disease (IBD) requiring infliximab frequently spend hours to attend treatment. Through quality improvement (QI) methodology, we aimed to shorten the time spent in the biologics infusion center using the accelerated infusion protocol and describe patient outcomes, safety, and associated cost savings. Methods: From September 2018 through December 2019, eligible IBD patients receiving infliximab were recruited. We implemented interventions including the accelerated infusion protocol, and modifying collection location of infliximab. Statistical process control charts were created. Patients' clinical outcome and cost savings data were analyzed using descriptive statistics and Pearson's chi‐square. Results: During the study period, a total of 60 patients with IBD receiving infliximab were recruited. A total of 315 infusions were administered—152 were under accelerated infusion protocol and 163 under standard protocol. The mean infliximab infusion time was reduced by 47%, from 2.4 h (142 ± 14 min) to 1.2 h (75 ± 10 min) (142 min vs 75 min, P < 0.001), with total time spent in the infusion center reduced by 52%, from 3.6 h (214 ± 25 min) to 1.7 h (102 ± 14 min) (214 vs 106 min, P < 0.001). Three mild infusion‐related reactions (3/152 = 1.97%) were recorded. Estimated cost savings over the 16‐month project period was SGD 6721.4 (nursing) and SGD 23 560 (patients). A high level of satisfaction (4.84 out of 5) with the protocol was reported. Conclusion: Our QI project shortened the infliximab infusion time and total time spent in the infusion center, without compromising patient safety. Estimated cost savings were substantial. The protocol helps reduce work productivity loss. Abstract : Through quality improvement (QI) methodology, we could shorten the time spent in the biologics infusion center using the accelerated infusion protocol. The project maintains patient safety. Estimated cost savings from the QI project are substantial.